Fabrication of agar-based tissue-mimicking phantom for the technical evaluation of biomedical optical imaging systems - Kim, Mingyu; Im, Seonghui; Park, Inyoung; Kim, Donghyeok; Kim, Eun Su; Joseph, James; Yoon, Jonghee (Current Applied Physics, 2024)
The development process of the optical systems for various biomedical applications typically involve evaluations of technical performance. One popular evaluation method is to use a reference object such as a phantom that exhibits similar optical properties of tissue. Fabrication of a consistent phantom with known optical properties, such as scattering and absorption, is essential for accurate technical evaluation of the optical system. This paper presents a protocol for fabricating an agar-based tissue-mimicking phantom, offering practical guidance to ensure consistent and reproducible phantom creation. In addition, optical setups that measure light information required for quantifying the optical properties via an inverse adding-doubling (IAD) method are discussed. We demonstrated the fabrication of phantoms with diverse scattering and absorption properties, and the IAD method successfully quantified the optical properties. Moreover, we employed the phantom to assess the imaging depth limitation of a hyperspectral imaging system, demonstrating potential usage of phantoms for performing technical evaluation.
Keywords: Adding doubling method; Biomedical optical imaging; Inverse adding-doubling; Light-tissue interaction; Optical imaging system; Phantoms; Scattering and absorption; Soft tissue; Technical evaluation; Tissue mimicking phantom; Light-tissue interaction; Optical system; Soft tissue; Technical evaluation; Tissue-mimicking phantom